EFEKTIVITAS PROBLEM-BASED LEARNING BERBASIS ETNOSAINS TERHADAP LITERASI SAINS SISWA SEKOLAH DASAR - Ningrum, Vianda Wulandari; Ghullam Hamdu; Erwin Rahayu Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to measure the effectiveness of the Problem-Based Learning (PBL) model integrated with ethnoscience in improving elementary school students’ scientific literacy. The research employed a quantitative approach with a One Group Pretest-Posttest Design. The participants were 31 fourth-grade students from SDN 1 Cintaratu and SDN 1 Cintajaya. Data were collected through a scientific literacy test covering three main indicators: explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting and using scientific information for decision-making. The findings revealed an increase in the average score from 65.68 (pretest) to 84.29 (posttest), with a moderate improvement category based on the N-gain analysis. Normality and homogeneity tests confirmed that the data met the requirements for parametric analysis. The paired sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest results. It is concluded that the application of the PBL model integrated with ethnoscience is effective in enhancing students’ scientific literacy, providing meaningful learning experiences that are contextual and relevant to local wisdom.